The acute right iliac fossa in hemophilic patients. - Gregorio, Luis A; Latourrette, Federico; Vila, Víctor M (Cirugía del Uruguay, 1977)
This review of case material concerning acute affection of right iliac fossa in hemophilic patients in the Hospital de Clínicas (University Hospital), comprises 7 cases. The condition is described together with the reasons for pre, per and post-operatory preparation based on cryoprecipitates and includes the parameters which gobern the activities of the surgical team in these emergencies.